"Get off my lawn!": Starting to understand territoriality in location based mobile games - Papangelis, Konstantinos; Metzger, Melvin; Sheng, Yiyang; Liang, Hai-Ning; Chamberlain, Alan; Khan, Vassilis-Javed (ACM, 2017)
With the increasing popularity of mobile video games, game designers and developers are starting to integrate geolocation information into such games. Although popular location-based games (LBGs) such as Ingress and Pokémon Go have millions of users, research still needs to be carried out to fully understand the ways in which such games impact upon a player’s interaction with other players and their physical surroundings. Consequently, there is limited knowledge on how user behavior can be addressed and drawn upon as a design resource to further engage and motivate players to play. To further understand this, we developed a LBG called CityConqueror and have conducted an in ’the wild’ study. This initial study starts to unpack the ways that human territoriality can be expressed in LBGs to facilitate player motivation, engagement and can support the integration of the game in the player’s daily life. Based on our findings we propose a series of design implications for LBGs. The primary purpose of this paper is to draw attention to the importance of territoriality and the way that this can be drawn upon as a resource for design.